Deeper insights into University Students' Perceptions about Peer Feedback in Second Language Writing: A Phenomenological Approach - Eda Duruk (Anı Publishing, 2016)
This phenomenological study was carried out to analyze whether students attending to a preparatory programme in a Turkish state university changed their perceptions about peer feedback after training them. The study was conducted with 25 students from the department of Medicine all of whom were attending the Mandatory English Preparatory Program in 2014 academic year. In this qualitative study, the research data were obtained from students via semi-structured interviews which were applied at the beginning and at the end of the study to have clear insights about students' perceptions on peer feedback before/after training them. During each training process, students were asked to write reflections after each feedback session, and each of them was analyzed to design the next training session. The data collected in the study were analyzed by content analysis technique and all the data were analyzed manually. The study findings revealed that training students on peer feedback yielded different results about their perceptions on peer feedback.